The autonomy and primary school clusters in Portugal: The point out of the proceeding - Alberto ALMEIDA (Ediciones Universidad de Salamanca, 2010)
From the 80s, in Portugal witnessed the approval of certain regulatory and publication of some studies on the administration and management of Portuguese schools that will culminate in 1998 with the approval of Decree-Law n.º 115-A/98, on May 4, which prescribed the school autonomy and decentralization as key aspects of a new organization of education, the aim being the achievement of democracy, equal opportunities and the quality of public education. It was definitely open to enable schools to group together according to their interests, affinities and geographical proximity. Underlying the formation of school clusters are important principles such as the realization of a sequential and linked path of children covered by compulsory education in a given geographical area and of overcoming the situation of isolation of certain schools. The grouping of establishments in schools should result in a dynamic and creative process, conducted by the schools themselves and according to their specific situation as part of a wider movement to strengthen the autonomy, the statement of an educational project and demand Discovery and partnerships. These dynamics have been implemented in very many counties of our country, were abruptly halted with the XV Constitutional Government, to impose a logic of vertical integration throughout the country, contrary to the provisions of Law of the Education and Decree-Law n.º 115A/98 of May 4. So, will emerge in the Portuguese educational map, vertical groupings of schools, now considered as new management units, with their own bodies and located in the school-based in each group. His appearance was part of a new policy of recentralization of power, accompanied by the transformation of each grouping, a new tier of devolved government, fostering a new form of control over the schools merged. The vertical groupings (many) only overlap in the same organizational unit sub-sets different professional interactions with sparse, usually about instrumental issues that do not involve an innovation to improve their professional practices.